2021
DOI: 10.9734/jpri/2021/v33i60b34650
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Pharmacological Treatment and Factors Affecting the Adherence among Hypertensive Patients Attending Primary Health Care Centers in Jazan, Saudi Arabia

Abstract: Background: Hypertension (HTN) is a major health problem globally because it can result in significant morbidity and a reduction in life expectancy, HTN is responsible for 9.4 million deaths annually, either due to heart attack or stroke with a contribution of 45% and 51%, respectively Objective: Evaluate the level of adherence to anti-HTN medications and which factors affect this adherence in the Jazan area Methodology: The researcher investigated the adherence to anti-hypertension (anti-HTN) medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Manfredini et al observed that married individuals had good control of their BP and were aware of their HTN, unlike single or divorced patients [ 33 ]. The most possible explanation for this difference is that married patients with HTN are more likely to receive support from their partners and health professionals about their health issues than unmarried patients [ 33 , 34 , 35 , 36 ]. Interestingly, in our study, we found that there was no significant difference between the married and single participants.…”
Section: Discussionmentioning
confidence: 99%
“…Manfredini et al observed that married individuals had good control of their BP and were aware of their HTN, unlike single or divorced patients [ 33 ]. The most possible explanation for this difference is that married patients with HTN are more likely to receive support from their partners and health professionals about their health issues than unmarried patients [ 33 , 34 , 35 , 36 ]. Interestingly, in our study, we found that there was no significant difference between the married and single participants.…”
Section: Discussionmentioning
confidence: 99%